Design and spirituality : a philosophy of material cultures - Walker, Stuart , 1955- (Routledge, 2021)
"Design and Spirituality examines the philosophical context of our current situation and its implications for design. It explores how modernity and our constricted notions of progress have contributed to today's crisis of values, and argues for a re-establishment and re-affirmation of self-transcending priorities, together with an ethos of moderation and sufficiency. A wide range of topics are covered, including material culture and spiritual teachings; sustainability and the spiritual perspective; traditional and indigenous knowledge; technology and spirituality; notions of meaningful design; and how particular material things can have deeper, symbolic significance. There are also reflections on areas such as the language of design; busyness and its relationship to wisdom; design and social disparity; and traditional sacred practices. While not avoiding issues that are controversial, and sometimes hard-hitting, Design and Spirituality gets to the heart of the key issues affecting us today and presents them in a highly readable and accessible format. The author is a leading thinker in the field and he presents his arguments in a manner that invites the reader to reflect and think about where we are going, why we are going there and what really matters"-- Provided by publisher